Social Media: Its Effects on Communicative Competence of Grade 12 HUMSS Strand Students at Bestlink College of the Philippines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Social media helps people to connect with the world, especially students who were born in an era where gadgets are prominent. The students used these platforms most likely because it is “up-to-date” with the world’s issues. Despite the positive effects of social media on the current era, it also has its hostile consequences, such as depleting the students’ competencies in manners of grammatical, socio-linguistic, discourse, and strategic. The debilitation of the communicative competence of the forthcoming generations is at high risk due to excessive and irresponsible use of social media. The study used a descriptive research design through a random sampling technique to determine the effects of social media on the communicative competence of Grade 12 Humanities and Social Sciences Strand students. Data were gathered through questionnaires, unstructured interviews, and informal observation. There were equal numbers of male and female respondents, mostly aged 18, with the scholastic rating in English ranging from 80 to 84. Most of the respondents used social media excessively for 2–6 h a day. Their communication skills are being debilitated because using social media lessens face-to-face interactions when chatting and sharing posts. It also affects the way individuals react to emotions, social clues, or nonverbal cues on account that they can easily relate and adapt to the trends in social media. The respondents’ self-esteem and self-confidence also get affected when someone talks to them in a degrading way. The results of this study showed that the importance of the word “media.” The researchers recommended that students should have media literacy in any kind of media modernization, empower themselves to ignite others in confronting social issues and trends wisely, develop higher-order thinking skills (analyze and weigh every information encountered), innovate educational platforms, use academic language and apply professional etiquette, and accept social media to establish beneficial connections and unfold multiple learning opportunities.
Keywords: communicative competence, depleting, media literacy, higher-order thinking skills